Efektivitas Psikoedukasi Manajemen Stres dan Literasi Keuangan terhadap Strategi Coping Wanita Menikah - Kharine Florenxia; Audrey Azhley Azmar; Celina Lysander; Riana Sahrani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program was initiated in response to the high psychological stress experienced by married women due to multiple role demands and family economic pressures. The program aimed to improve stress management skills through adaptive coping strategies, self-care, and basic financial literacy. It was conducted at RPTRA Duta Mas, Jelambar Baru, West Jakarta, using interactive psychoeducation, financial management simulation games, self-reflection activities, and pre-test and post-test evaluations with the Perceived Stress Scale and Brief COPE involving 29 married women. The results showed that most participants experienced reduced stress levels and improved adaptive coping abilities in managing problems and emotional responses. Participants also demonstrated better understanding of basic financial management, prioritizing needs, and the importance of self-care. Overall, the program was effective in enhancing stress management skills and supporting the psychological well-being of married women through a practical and comprehensive approach.